2011
DOI: 10.1016/j.neuron.2011.05.037
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Is an Activity-Dependent Regulator of Target Neuron Intrinsic Excitability

Abstract: SummaryActivity-dependent changes in synaptic strength are well established as mediating long-term plasticity underlying learning and memory, but modulation of target neuron excitability could complement changes in synaptic strength and regulate network activity. It is thought that homeostatic mechanisms match intrinsic excitability to the incoming synaptic drive, but evidence for involvement of voltage-gated conductances is sparse. Here, we show that glutamatergic synaptic activity modulates target neuron exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
122
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(128 citation statements)
references
References 80 publications
6
122
0
Order By: Relevance
“…PrP Sc was detected after proteinase K digestion 7 . Whole-cell recordings were done in acute hippocampal slices to measure synaptic transmission 31 . Global translation levels were detected using [ 35 S]methionine incorporation in acute hippocampal slices; translations of specific transcripts in polysomal fractions from hippocampi were analysed by northern blotting 32 .…”
Section: Methodsmentioning
confidence: 99%
“…PrP Sc was detected after proteinase K digestion 7 . Whole-cell recordings were done in acute hippocampal slices to measure synaptic transmission 31 . Global translation levels were detected using [ 35 S]methionine incorporation in acute hippocampal slices; translations of specific transcripts in polysomal fractions from hippocampi were analysed by northern blotting 32 .…”
Section: Methodsmentioning
confidence: 99%
“…The activity of the delayed rectifying K+ channels is an important determinant of the activation threshold in dendrites and is thought to have a major impact on neuronal plasticity (Sjostrom et al, 2008). Kv channels have been shown to participate in the regulation of the neuronal excitability of CA3 hippocampal neurons in response to synaptic activity through a NO-dependent mechanism (Steinert et al, 2011). Previously, we have reported that Wnt-5a induces NO production in hippocampal neurons to regulate the surface expression of NMDARs (Muñoz et al, 2014); our results suggest a potential common mechanism underlying Wnt-5a-dependent changes in post-synaptic excitability and plasticity.…”
Section: Effect Of Wnt-5a Upon Hippocampal Synaptic Potentials Is Supmentioning
confidence: 52%
“…NO signaling also contributes to the fine tuning of ion channel activity and therefore neuron excitability (Steinert et al, 2011). The family of Kv channels, when deregulated, has been linked to CNS diseases including hereditary epilepsy (Otto et al, 2009), episodic ataxia and Alzheimer's disease (Colom et al, 1998;Shieh et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In peripheral tissues this enzyme is mainly, but not exclusively, expressed in macrophages. In the CNS, NOS-2 is 25 expressed in microglia and astroglia, and its generation of NO has been implicated in the pathogenesis of various insults as well as in neurological disorders (Brown and Neher 2010, Murphy 2000, Steinert et al 2011. Upregulation of iNOS has been implicated in tissue damage in MS and EAE (Raivich and Banati 2004).…”
Section: Nitric Oxide Synthasesmentioning
confidence: 99%